Motion Graphic sebagai Media Informasi Desain Komunikasi Visual (DKV) Peminatan Designpreneur - Prajana, Adya; Syafikarani, Aisyi; Wiba Pamela, Apsari (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
The development of information and communication technology today has made it easier for people to obtain information. People can access information anytime and anywhere without being limited by space and time. Currently, Visual Communnication Design (DKV) Designpreneur does not have information media that can explain the specialization profile to basic level students who will choose a specialization when they move up to level 2. As a result, many basic level students are confused and decide not to choose the DKV Designpreneur specialization. The data collection methods used in the design are interviews, observation, literature study, and will be analyzed using STP, SWOT analysis and using the Three Act Structure design method for the structure of the information to be conveyed. This research aims to design motion graphic videos as information media for the DKV Designpreneur specialization aimed at elementary level students in the DKV Study Program, Telkom University. So the results of this research are expected to 1) be able to provide information regarding the DKV Designpreneur specialization through motion graphic media. 2) Massive video distribution must be carried out by all DKV Designpreneur students and lecturers, so that this video reaches and can be watched by elementary level students.